2009
DOI: 10.1108/09615530910938416
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of wetting fluid spread into porous media

Abstract: Purpose -The purpose of this paper is to develop a general numerical solution for the wetting fluid spread into porous media that can be used in solving of droplet spread into soils, printing applications, fuel cells, composite processing. Design/methodology/approach -A discrete capillary network model based on micro-force balance is numerically implemented and the flow for an arbitrary capillary number can be solved. At the fluid interface, the boundary condition that accounts for the capillary pressure jump … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…For very large droplets and highly heterogeneous media, the multiphase flow can be developed later on during the primary spread. 24 During the secondary spread, the liquid from the large pores flows into small pores due to the capillary force. At the beginning of the secondary spread, the large pores filled by liquid that are closer to the free interface are emptied; as the secondary spread proceeds, the overall number of large pores filled by liquid decreases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For very large droplets and highly heterogeneous media, the multiphase flow can be developed later on during the primary spread. 24 During the secondary spread, the liquid from the large pores flows into small pores due to the capillary force. At the beginning of the secondary spread, the large pores filled by liquid that are closer to the free interface are emptied; as the secondary spread proceeds, the overall number of large pores filled by liquid decreases.…”
Section: Resultsmentioning
confidence: 99%
“…At the end of primary spread, the imprint wetted area is around A w Ϸ 23 mm 2 which is different ͑it is larger͒ from the droplet base area that is calculated from the droplet base radius r 0 = 1.4 mm, ͑r 0 2 p = 6.2 mm 2 ͒. Measuring A w and d p at the end of the primary spread and assuming the droplet imprint is a spheroid in shape due to the pore cross links and droplet base finite size, 11,[24][25][26] it is found that the liquid mass balance for a single-phase flow is satisfied and the void volume in wetted sand ͑droplet imprint͒ is fully saturated by the liquid phase. Hence, V 0 can be expressed as…”
Section: B Inner Solutionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, adopting the spheroid geometry [13], the imprint shape is given with two half-axes lengths a and b…”
Section: Problem Formulationmentioning
confidence: 99%